Dribble deficit - A novel measurement approach to assess dribbling speed independent of sprinting speed in basketball - Scanlan, A. T.; Wen, N.; Spiteri, T.; Guy, J. H.; Dalbo, V. J. (Journal of Australian Strength and Conditioning, 2017)
Dribbling speed has been identified as an important attribute of basketball game-play during high-speed transitions of the ball down the court and attacking plays at the basket. In turn, it is imperative that basketball practitioners have suitable tests at their disposal to precisely assess dribbling speed. Traditional tests to assess dribbling speed predicated on total performance times are overtly influenced by sprinting speed. Therefore, this study describes a novel approach to overcome this limitation termed Dribble Deficit, and aims to examine the relationships between sprinting and dribbling speed during linear and change-of-direction (COD) tasks measured using total performance time and Dribble Deficit.